Cutting edge approaches to detecting brain mosaicism associated with common focal epilepsies: implications for diagnosis and potential therapies. (2nd November 2021) - Ye, Zimeng; Bennett, Mark F.; Bahlo, Melanie; Scheffer, Ingrid E.; Berkovic, Samuel F.; Perucca, Piero; Hildebrand, Michael S.
ABSTRACT: Introduction: Mosaic variants arising in brain tissue are increasingly being recognized as a hidden cause of focal epilepsy. This knowledge gain has been driven by new, highly sensitive genetic technologies and genome-wide analysis of brain tissue from surgical resection or autopsy in a small proportion of patients with focal epilepsy. Recently reported novel strategies to detect mosaic variants limited to brain have exploited trace brain DNA obtained from cerebrospinal fluid liquid biopsies or stereo-electroencephalography electrodes. Areas covered: The authors review the data on these innovative approaches published in PubMed before 12 June 2021, discuss the challenges associated with their application, and describe how they are likely to improve detection of mosaic variants to provide new molecular diagnoses and therapeutic targets for focal epilepsy, with potential utility in other nonmalignant neurological disorders. Expert opinion: These cutting-edge approaches may reveal the hidden genetic etiology of focal epilepsies and provide guidance for precision medicine.